Toward the Existence of a Sympathetic Neuroplasticity Adaptive Mechanism Influencing the Immune Response. A Hypothetical View—Part II - Bottasso, Emanuel (Frontiers in Endocrinology, 2019)
In the preceding work a hypothesis on the existence of a specific neural plasticity program from sympathetic fibers innervating secondary lymphoid organs was introduced. This proposed adaptive mechanism would involve segmental retraction of noradrenergic terminals during immune system (IS) activation followed by regeneration once the IS returns to the steady state. Starting from such view, this second part presents clinical and experimental evidence allowing to envision that this sympathetic neural plasticity mechanism is also operative on inflamed non-lymphoid peripheral tissues. Importantly, sympathetic nervous system regulates most of the physiological bodily functions, ranging from cardiovascular, respiratory and gastro-intestinal functions to endocrine and metabolic ones, among others. Thus, it seems sensible to think that compensatory programs should be put into place during inflammation in non-lymphoid tissues as well, to avoid the possible detrimental consequences of a sympathetic blockade. Nevertheless, in many pathological scenarios like severe sepsis, chronic inflammatory diseases or maladaptive immune responses, such compensatory programs against noradrenergic impairment would fail to develop. This would lead to a manifest sympathetic dysfunction in the above-mentioned settings, partly accounting for their underlying pathophysiological basis; which is also discussed. The physiological/teleological significance for the whole neural plasticity process is postulated, as well.